MENATA ULANG PENYELENGGARAAN PEMERINTAHAN DAERAH MELALUI PENDEKATAN MANAJEMEN PUBLIK - Kristian Widya Wicaksono (Jurnal Paradigma (JP), 2017)
Since year 2001 the implementation of decentralization is necessary in Indonesia to strengthen the capacity of local government. It is kind of transformation authority from the central government to the local government. But practically, most of the local government did not able to implement it completely. The weakness of local government in implementing local authority policy is the pattern of governance. So that is why, to accelerate the advantages of decentralization policy for the society, strengthening the managerial capacity is needed using public management approach. This article tries to illustrate about the public management in the context of executing local government.